2016
DOI: 10.1007/978-3-319-42324-1_47
|View full text |Cite
|
Sign up to set email alerts
|

Milliseconds Matter: Temporal Order of Visuo-tactile Stimulation Affects the Ownership of a Virtual Hand

Abstract: The sense of body ownership, that one's body belongs to oneself, is a result of the integration of dierent sensory streams. This sense however is not error-free; in 1998 Botvinick and Cohen [3] showed the rubber hand illusion (RHI), an illusion that made a subject feel a rubber hand as their own. An important factor to induce the illusion is the timing of the applied visual and tactile stimulation to the rubber hand. Temporal delays greater than 500ms eliminate the illusory ownership. This study investigates p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Other studies have found similar results (e.g., Ehrsson, Holmes, & Passingham, 2005;Ehrsson, Wiech, Weiskopf, Dolan, & Passingham, 2007). Usually, a window longer than 500 ms will not induce the illusion (Zoulias, Harwin, Hayashi, & Nasuto, 2016).…”
Section: Experimentally Induced Bodysupporting
confidence: 61%
“…Other studies have found similar results (e.g., Ehrsson, Holmes, & Passingham, 2005;Ehrsson, Wiech, Weiskopf, Dolan, & Passingham, 2007). Usually, a window longer than 500 ms will not induce the illusion (Zoulias, Harwin, Hayashi, & Nasuto, 2016).…”
Section: Experimentally Induced Bodysupporting
confidence: 61%
“…An important factor of the experiments mentioned previously is the timing of the applied stimuli. Zoulias et al [147] emphasized the sensitivity of the illusion to this factor by showing that small delays have negative effects, especially when tactile stimulation precedes visual signal. This influence of synchrony was found in the AR version of the VHI elaborated by Gilbers [1], but its importance has not been assessed as deeply as in VR.…”
Section: Other Important Cues In Armentioning
confidence: 99%